EXPLORING STUDENTS’ RESPONSES TO THE “MISSYOU” LYRIC GAME ON LEARNING LISTENING - hesty puspita sari (Jurnal Bahasa Lingua Scientia, 2022)
The purpose of this study is to see how students react to using the "Missyou" Lyric Game in listening activity. This study uses a qualitative research design. The participants in this study were 20 students from SMPN 1 Srengat who were chosen at random. A questionnaire was used to gather information. The purpose of the questionnaire is to collect student responses and determine whether the "Missyou" Lyric Game model explores and develops students' listening ability as an alternative media for learning to listen. The results revealed that 81,65 percent of respondents agreed that song lyrics may enhance their listening skills.